Hubungan Sikap Ibu dengan Ketepatan Waktu Pemberian Imunisasi Campak pada Bayi Di Desa Sungai Jalau Wilayah Kerja UPT Puskesmas Sawah Tahun 2022 - Parmin, Joria; Lubis, Dumasari; Mustika Sari, Umi (Evidence Midwifery Journal, 2023)
In determining the success of providing measles immunization, it can be seen from the even and high coverage of measles immunization. Measles immunization must be carried out in accordance with the rules so that it functions well so that it works optimally, while immunization that is not timely does not work optimally, causing KLBPD3I and failure to implement immunization evenly. The aim of this research is the relationship between maternal attitudes and the timeliness of measles immunization in Sungai Jalau Village, UPT Puskesmas Sawah Working Area. The research design used cross sectional. The sample for this study was mothers who had babies aged 9–12 months using a total sampling technique. The data collection tool used is a questionnaire. Data analysis using a questionnaire. The research results showed that there was a relationship between maternal attitudes and the timeliness of measles immunization with a p value of 0.002 (<0.05). Based on the results of the chi square test, it was found that 26 respondents behaved well, with 18 people having immunization on time and 8 people not on time, while 12 people behaved less well, with 11 people not being on time and 1 person being on time. With the results of this study, researchers hope that all mothers will be able to provide measles immunization to their children according to the specified time and will be able to understand the importance of measles immunization for their children